Association of Toll-Like Receptor Signaling and Reactive Oxygen Species: A Potential Therapeutic Target for Posttrauma Acute Lung Injury. (30th June 2010) - Xiang, Meng; Fan, Janet; Fan, Jie
Abstract : Acute lung injury (ALI) frequently occurs in traumatic patients and serves as an important component of systemic inflammatory response syndrome (SIRS). Hemorrhagic shock (HS) that results from major trauma promotes the development of SIRS and ALI by priming the innate immune system for an exaggerated inflammatory response. Recent studies have reported that the mechanism underlying the priming of pulmonary inflammation involves the complicated cross-talk between Toll-like receptors (TLRs) and interactions between neutrophils (PMNs) and alveolar macrophages (AMϕ ) as well as endothelial cells (ECs), in which reactive oxygen species (ROS) are the key mediator. This paper summarizes some novel mechanisms underlying HS-primed lung inflammation focusing on the role of TLRs and ROS, and therefore suggests a new therapeutic target for posttrauma ALI.